ON NEW APPROACHES TO ESTIMATION OF INFLUENCE OF THE ENTERPRISE HUMAN CAPITAL CHARACTERISTICS ON DYNAMICS OF ITS ECONOMICAL INDICES - N. V. Andrianov; A. N. Chiehko (Литьë и металлургия, 2007)
The structural model of industrial enterprise is presented, for which the differential form of interrelations between characteristics of human capital and characteristics of economical indices is developed.